A visão linguística do Além egípcio antigo na tradução para português e inglês (Studia Iberystyczne, 2019)
The Linguistic View of the Ancient Egyptian Beyond in translation into Portuguese and EnglishThe linguistic worldview of the Beyond in the religious thought of the ancient Egyptians is clearly distinguished from the beliefs of other ancient nations. The author of the paper intends to analyse it as contextualised in the Pyramid Texts, based on her translations of the diagnostic spells. This is an analysis of the linguistic view in the translation from the hieroglyphic Egyptian into Portuguese, making some comparisons of the translations of the spells into English. Some obstacles or difficulties in this translation are evinced.Using methods of analysis of the Egyptian language, we may better understand the way of thinking of the Egyptians. The linguistic worldview method, namely the verbalised interpretation of reality which was developed by J. Bartmiński, his colleagues and collaborators, can be exceptionally useful. By means of an in-depth linguistic analysis of the fragments of the world’s oldest religious texts translated into contemporary languages, one can develop a much more complete scholarly discussion.